2007
DOI: 10.1111/j.1365-2966.2006.11245.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic search for new SW Sextantis stars in the 3-4 h orbital period range - I

Abstract: We report on time‐resolved optical spectroscopy of 10 non‐eclipsing nova‐like cataclysmic variables in the orbital period range between 3 and 4 h. The main objective of this long‐term programme is to search for the characteristic SW Sextantis behaviour and to eventually quantify the impact of the SW Sex phenomenon on nova‐likes at the upper boundary of the orbital period gap. Of the 10 systems observed so far, HL Aqr, BO Cet, AH Men, V380 Oph, AH Pic and LN UMa are identified as new members of the SW Sex class… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 69 publications
5
88
2
Order By: Relevance
“…The results obtained are reminiscent of the radial velocity curve of the SW Sex star V380 Oph, displayed in fig. 13 of Rodríguez‐Gil, Schmidtobreick & Gänsicke (2007a), which shows a shorter time‐scale variation superimposed on the sinusoidal orbital modulation. If the same behaviour is displayed by Hα075648 and Hα122105, then we observed less than one orbital cycle in any one night.…”
Section: Results For Individual Systemsmentioning
confidence: 96%
“…The results obtained are reminiscent of the radial velocity curve of the SW Sex star V380 Oph, displayed in fig. 13 of Rodríguez‐Gil, Schmidtobreick & Gänsicke (2007a), which shows a shorter time‐scale variation superimposed on the sinusoidal orbital modulation. If the same behaviour is displayed by Hα075648 and Hα122105, then we observed less than one orbital cycle in any one night.…”
Section: Results For Individual Systemsmentioning
confidence: 96%
“…All the features described above are defining characteristics of the SW Sex stars (see Thorstensen et al 1991b; Rodríguez‐Gil, Schmidtobreick & Gänsicke 2007). Even though each system exhibits its own peculiarities (e.g.…”
Section: Sw Sex Membershipmentioning
confidence: 99%
“…The ingress to the eclipse is steeper than the egress. Such an eclipse shape is very common for SW Sex stars (Thorstensen et al 1991) and was a defining feature of the class until it was later revealed that there are also non-eclipsing SW Sex stars (Rodríguez-Gil et al 2007b).…”
Section: Photometrymentioning
confidence: 99%